EMBEDDING THE VALUES OF JUSTICE, EQUALITY AND ACCEPTANCE OF DIFFERENCES IN STUDENTS: A LITERATURE REVIEW OF INCLUSIVE EDUCATION STRATEGIES IN INDONESIA - Gunawan Widjaja; Songga Aurora Abadi; Michael Matthew (International Journal of Teaching and Learning, 2025)
This research aims to examine inclusive education strategies in instilling values of justice, equality and acceptance of differences in students in Indonesia through a literature review. Inclusive education is seen as an approach that provides equal learning opportunities for all children, regardless of background, physical, mental or social conditions. Through strategies such as adaptive learning, collaboration between teachers, parents and communities, and the development of a diversity-friendly school culture, inclusive education is able to create an equitable learning environment that respects diversity. The review shows that the implementation of inclusive education strategies has a positive impact on students' social, academic and character development and reduces stigma and discrimination in the school environment. However, challenges such as limited resources, lack of teacher training and social stigma remain major obstacles. Therefore, a sustained commitment from all stakeholders is needed to strengthen training, provide adequate facilities and conduct socialisation and advocacy so that inclusive education can run optimally and sustainably.